PENGARUH PEMANFAATAN KOPERASI TERHADAP TINGKAT KESEJAHTERAAN WARGA PADA KOPERASI SIMPAN PINJAM “KARYA AGUNG” BOJONEGORO - Rifky Ardhana Kisno Saputra; Endah Yuliani (HUMANIS: Jurnal Ilmu-Ilmu Sosial dan Humaniora, 2019)
Cooperative business entities have the main goal not to seek profit but to serve members of the cooperative to be more prosperous based on the principle of family. The savings and loan cooperative "Karya agung" collects funds from its members who then redistribute the funds to its members. This study aims to provide an overview of the effect of cooperative use on the level of welfare of citizens. The taking technique used in this research is random sampling technique. The method of data collection used is to use questionnaires, interviews and documentation. The analysis method uses correlation analysis techniques with the product moment. Calculation of the value of which states that there is an influence between the use of savings and loan cooperatives to the level of welfare of citizens.